Development of thoracic injury risk functions for the THOR ATD. (September 2017) - Poplin, Gerald S.; McMurry, Timothy L.; Forman, Jason L.; Ash, Joseph; Parent, Daniel P.; Craig, Matthew J.; Song, Eric; Kent, Richard; Shaw, Greg; Crandall, Jeff
Highlights: We present a method for estimating injury risk using multi-point chest deflections. A data reduction technique was used to generate a combined deflection metric. Survival analyses models with resultant deflection were consistently better. Two deflection metrics resulted in the most appropriate injury risk models. Abstract: The Test Device for Human Occupant Restraint (THOR) 50th percentile male anthropomorphic test device (ATD) aims to improve the ability to predict the risk of chest injury to restrained automobile occupants by measuring dynamic chest deflection at multiple locations. This research aimed to describe the methods for developing a thoracic injury risk function (IRF) using the multi-point chest deflection metrics from the 50th percentile male THOR Metric ATD with the SD-3 shoulder and associating to post-mortem human subjects (PMHS) outcomes that were matched on identical frontal and frontal-oblique impact sled testing conditions. Several deflection metrics were assessed as potential predictor variables for AIS 3+ injury risk, including a combined metric, called PC Score, which was generated from a principal component analysis. A parametric survival analysis (specifically, accelerated failure time (AFT) with Weibull distribution) was assessed in the development of the IRF. Model fit was assessed using various modeling diagnostics, including the area under the receiver operating characteristic curve (AUC). Models based on resultant deflection consistently exhibited improved fit compared to models based on x-axis deflection or chord deflection. Risk functions for the THOR PC Score and Cmax (maximum resultant deflection) were qualitatively equivalent, producing AUCs of 0.857 and 0.861, respectively. Adjusting for the potential confounding effects of age, AFT survival models with Cmax or PC Score as the primary deflection metric resulted in the THOR injury risk models with the best combination of biomechanical appropriateness, potential utility and model fit, and may be recommended as injury predictors.